Männlichkeiten im Wandel: Zur Regierung von Geschlecht in der deutschen und schwedischen Debatte um ›Männer in Kitas‹ - Diewald, Irmgard (transcript, 2018)
Men in child care centers – about the recruitment of male preschool teachers in Germany and Sweden as a moment of discursive negotiation of gender relations.